The Impact of Memrise Application on Students’ Speaking Skills (A Quasi-Experimental Study at Islamic junior high school) - Alfina Rahmadewi; Desi Nahartini (Universitas Islam Negeri Palopo, 2025)
The purpose of this study was to obtain empirical data on the effect of the Memrise application in improving students' speaking skills, particularly seventh-grade students at Islamic Junior High School. This study used a quasi-experimental design involving two groups: an experimental class and a control class. Both groups consisted of seventh-grade students, each with 32 participants. Data were collected through pre-tests, treatments, and post-tests. The treatment was conducted over four meeting. Statistical analysis was performed using IBM SPSS 25, including normality and homogeneity tests, independent sample t-tests, and effect size tests. The results showed that the experimental class experienced a significant increase in their speaking scores compared to the control class. This study was tested using a t-test with a p-value on the post-test of less than 0.05, indicating significant results. Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. In addition, the effect size value of 1.109 indicated a strong effect, proving that the Memrise application had a significant and positive impact on the speaking skills of seventh-grade students at Islamic Junior High School.